The tipping point : how little things can make a big difference - Gladwell, Malcolm, 1963- (Abacus, 2009)
In this book, Malcolm Gladwell explains and analyses the tipping point, that magic moment when ideas, trends and social behaviour cross a threshold, tip and spread like wildfire.